2017
DOI: 10.4047/jap.2017.9.3.176
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of marginal and internal gaps of Ni-Cr and Co-Cr alloy copings manufactured by microstereolithography

Abstract: PURPOSEThe purpose of this study was to evaluate the marginal and internal gaps of Ni-Cr and Co-Cr copings, fabricated using the dental µ-SLA system.MATERIALS AND METHODSTen study dies were made using a two-step silicone impression with a dental stone (type IV) from the master die of a tooth. Ni-Cr (NC group) and Co-Cr (CC group) alloy copings were designed using a dental scanner, CAD software, resin coping, and casting process. In addition, 10 Ni-Cr alloy copings were manufactured using the lost-wax technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Mikrotek N/S a [36] 3Shape D700 [38,42,44,48] Yenadent N/S [36] BEGO Wirobond 280 [37,44] BEGO Fornax [39,45,46] 3Shape D800 [45,46] Yenadent DC40 [43] BEGO Wirobond C [40,48,49,52] BEGO Nautilus CC [44,52] 3Shape D640 [52] Concept laser M1 [36,38,42,44] BEGO N/S [36] Renfert N/S [40] 3Shape N/S [37] Eosint M270 [13,39,43,46,48] EOS MP1 [39] N/S [37,38,41,48,49] 3M Lava [51] BEGO N/S [40] EOS SP2 [13,42,43,46,48] Straumann Cares [47,50] Straumann milling [47,50] Straumann Coron [47,…”
Section: Casting Machine Cad System Cam System Alloymentioning
confidence: 99%
“…Mikrotek N/S a [36] 3Shape D700 [38,42,44,48] Yenadent N/S [36] BEGO Wirobond 280 [37,44] BEGO Fornax [39,45,46] 3Shape D800 [45,46] Yenadent DC40 [43] BEGO Wirobond C [40,48,49,52] BEGO Nautilus CC [44,52] 3Shape D640 [52] Concept laser M1 [36,38,42,44] BEGO N/S [36] Renfert N/S [40] 3Shape N/S [37] Eosint M270 [13,39,43,46,48] EOS MP1 [39] N/S [37,38,41,48,49] 3M Lava [51] BEGO N/S [40] EOS SP2 [13,42,43,46,48] Straumann Cares [47,50] Straumann milling [47,50] Straumann Coron [47,…”
Section: Casting Machine Cad System Cam System Alloymentioning
confidence: 99%
“…Restorations consisting of more than four implants were reported to show limited accuracy on both optical and conventional impressions ( Gedrimiene et al, 2019 , Rech-Ortega et al, 2019 ). Some studies have revealed that conventional impressions may be more appropriate for long-span or full-arch restorations ( Ahlholm, et al, 2018 , Anan and Al-Saadi, 2015 , Kim et al, 2017a , Mangano et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ni-Cr has low corrosion resistance and is not biocompatible because nickel can cause allergic reactions. In addition, the addition of beryllium to Ni-Cr which functions as a hardener, grain structure refiner, and to reduce the combustion temperature is carcinogenic, but is still within the clinically acceptable threshold of 0.002 ppm 3 . Concerns about the toxicity due to the use of nickel and beryllium, although still within clinically accepted limits, have spurred researchers to develop Co-Cr alloys as an alternative that can be used in porcelain metal crown restorations.…”
Section: Introductionmentioning
confidence: 99%
“…The acceptable vertical marginal adaptation of a restoration ranges from 10 -160 µm. Clinically, for the long-term resilience of a restoration, the acceptable marginal adaptation difference is 40-120 µm 8 . In selecting the type of alloy for coping, one of several important factors to consider is the dimensional accuracy of the resulting coping.…”
Section: Introductionmentioning
confidence: 99%